Pengembangan Lembar Kerja Siswa (LKS) Berbasis Problem Based Learning (PBL) Materi Virus Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Di SMA - Haryono, Agus; Sudyana, I Nyoman; Miranda, Yula; Sari, Bunga Nilam (JURNAL PENDIDIKAN, 2023)
This study aims to develop Student Worksheets (LKS) based on Problem Based Learning (PBL) to improve students' critical thinking skills based on the characteristics of LKS as well as student responses and teacher responses to PBL-based LKS products developed. The research site at SMAS PGRI 2 in Sampit class X with a sample of 45 students, trial I as many as 15 students and trial II as many as 30 students.Research method of ADDIE model development ( analysis, design, development, implementation, evaluation). One group pretest-posttest design. The results showed that the characteristics of the LKS product developed were composed of the syntax of the Problem Based Learning (PBL) model with indicators of critical thinking skills able to increase students' critical thinking on viral material. PBL-based student worksheets can improve students' critical thinking skills with an average N-gain of trial I of 0.58 and trial II of average N-gain of 0.67 with moderate categories. The teacher's response to PBL-based LKS in trial I percentage value above 61% category was quite good and trial II percentage value above 90% category was very good. The students' response after using LKS in trial I was quite good with a percentage value above 67% and in the phase II trial the response was very good with a percentage value above 82%.